2010
DOI: 10.1534/genetics.110.115501
|View full text |Cite
|
Sign up to set email alerts
|

The Synaptonemal Complex Shapes the Crossover Landscape Through Cooperative Assembly, Crossover Promotion and Crossover Inhibition During Caenorhabditis elegans Meiosis

Abstract: The synaptonemal complex (SC) is a highly ordered proteinaceous structure that assembles at the interface between aligned homologous chromosomes during meiotic prophase. The SC has been demonstrated to function both in stabilization of homolog pairing and in promoting the formation of interhomolog crossovers (COs). How the SC provides these functions and whether it also plays a role in inhibiting CO formation has been a matter of debate. Here we provide new insight into assembly and function of the SC by inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
89
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(96 citation statements)
references
References 56 publications
6
89
1
Order By: Relevance
“…This and findings from other organisms (Wojtasz et al 2009;Hayashi et al 2010;Kauppi et al 2013) have led to the hypothesis that homologous chromosomes that successfully engage one another largely stop making DSBs (Kauppi et al 2013;Keeney et al 2014;Thacker et al 2014). This negative feedback regulation, which (Thacker et al 2014), is proposed to be distinct from Tel1-mediated DSB control .…”
Section: Altered Spo11-oligo Sizes In Tel1 Mutantsmentioning
confidence: 99%
“…This and findings from other organisms (Wojtasz et al 2009;Hayashi et al 2010;Kauppi et al 2013) have led to the hypothesis that homologous chromosomes that successfully engage one another largely stop making DSBs (Kauppi et al 2013;Keeney et al 2014;Thacker et al 2014). This negative feedback regulation, which (Thacker et al 2014), is proposed to be distinct from Tel1-mediated DSB control .…”
Section: Altered Spo11-oligo Sizes In Tel1 Mutantsmentioning
confidence: 99%
“…Recent work has demonstrated that the C. elegans SC central region proteins are important not only for promoting the formation of meiotic COs, but also for limiting their numbers by contributing to CO interference (Hayashi et al 2010;Libuda et al 2013). Inherent in the concept of CO interference is the ability of a nascent CO to change the environment in which it occurs in a manner that inhibits other recombination events in its vicinity from maturing into COs.…”
Section: Implications Of a Two-state View Of The Scmentioning
confidence: 99%
“…It is possible that this increased efficiency reflects our use of the C. elegans strain AZ212 as host for feeding RNAi, as this strain has been demonstrated to be more sensitive to RNAi. 28 However, it also likely reflects the direct advantage of targeted screening (the genes assayed were preselected for likely involvement in fertility); further, smaller-scale screens such as this also allow increased sensitivity of assays-by screening only a limited number of candidates, we can carry out assays allowing detection of more modest reductions in fertility than could be assayed in genomewide screening.…”
Section: Resultsmentioning
confidence: 99%
“…Feeding RNAi was done in strain AZ212 (reported to have higher sensitivity to RNAi). 28 Standard strain propagation for proteomics took place at 16 C on nematode growth medium (NGM) plates seeded with E. coli strain OP50; liquid culture was done in S medium supplemented with OP50 at 25 C. 30 Feeding RNAi was carried out at 20 C.…”
Section: Methods/materialsmentioning
confidence: 99%